Internal Environment Relating Human Resource Development of laksam Subdistrict Administrative Organization, Ban Praew District, Samutsakhon Province - Meenakorn, Chanpen (Journal of Humanities and Social Sciences Thonburi University, 2022)
The purpose of this research were: (1) to study the organization’s internal environment related to the human resource development of laksam Subdistrict Administrative Organization, Ban Praew District, Samutsakhon Province, (2) to study the level opinions of employees toward the internal environmental organization related to the human resource development of laksam Subdistrict Administrative Organization, Ban Praew District, Samutsakhon Province, and (3) to provide the recommendations to development of human resources of laksam Subdistrict Administrative Organization, Ban Praew District, Samutsakhon Province in order to adapt themselves appropriately to suit the environment in the organization. The questionnaire mail survey was used as research instrument. The statistics employed for data analysis were percentage, mean, standard deviation, and Pearson’s product moment correlation coefficient. The results of hypothesis testing found that environment factors with six aspects were positively related to the human resource development at a high level.